2015
DOI: 10.1186/s12913-015-0931-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the decision that women make on their mode of delivery: the Health Belief Model

Abstract: BackgroundChildbirth is regarded as an important life event for women, and growing numbers of them are making the choice to give birth by Caesarean Delivery. The aim of this study was to identify the factors influencing the decision that women make on their mode of delivery, underpinned by the Health Belief Model.MethodsThis was a cross-sectional study. Hong Kong Chinese women aged 18–45, who were pregnant or had given birth within the last three years were recruited. The participants were asked to complete a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 45 publications
5
73
0
2
Order By: Relevance
“…This is consistent with some studies that have reported an increased tendency for caesarean section among women with higher educational level (19) but inconsistent with other reports that more educated women choose vaginal delivery (20). Although some studies have indicated that women who live in a city and who are in employment are more likely to choose caesarean section (13,21,22), these factors have less effect than other demographic factors on choosing caesarean section.…”
Section: Maternal Factorssupporting
confidence: 49%
“…This is consistent with some studies that have reported an increased tendency for caesarean section among women with higher educational level (19) but inconsistent with other reports that more educated women choose vaginal delivery (20). Although some studies have indicated that women who live in a city and who are in employment are more likely to choose caesarean section (13,21,22), these factors have less effect than other demographic factors on choosing caesarean section.…”
Section: Maternal Factorssupporting
confidence: 49%
“…With 28% of the Australian population born overseas (ABS, ), Australia is also one of the most multicultural countries in the world. Beliefs, values, and traditions influence women's attitudes and decisions about modes of delivery (Latifnejad, Zakerihamidi, & Merghati, ; Loke, Davies, & Li, ; Ugwu & de Kok, ). Women may prefer to have a CS for various reasons, such as fear of labour pain and perineal tearing (Loke et al, ), or because they consider CS to be a prestigious mode of birth (Latifnejad et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Beliefs, values, and traditions influence women's attitudes and decisions about modes of delivery (Latifnejad, Zakerihamidi, & Merghati, ; Loke, Davies, & Li, ; Ugwu & de Kok, ). Women may prefer to have a CS for various reasons, such as fear of labour pain and perineal tearing (Loke et al, ), or because they consider CS to be a prestigious mode of birth (Latifnejad et al, ). Women may also refuse CS because of the socio‐cultural norms about gender and religious ideologies (Ugwu & de Kok, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many theories about how delivery should be, as well as many doctors in favor of cesarean and many other advocates of natural childbirth. It should be noted that vaginal delivery is a natural process, the woman's body is hormonally and mechanically prepared to be able to carry it out even without medical intervention Loke, Davies, and Li 2015). However, there may be unforeseen events at the time of delivery that require professionals to make the decision to perform a cesarean section such as abnormal heart rate of the baby, position of the baby that hinders natural childbirth, problems of the baby's development such as spina bifida or hydrocephalus, some cases of multiple pregnancy, genital infection of the mother, placenta previa or placental abruption and prolapse of umbilical cord which all considered as indications for cesarean section, in general, any situation that endangers the life of the baby or the mother will be indicative for a cesarean section (Ahmed, Alsheeha, and Alsammani 2013;Molina-Sosa et al, 2004) On the other hand, there are women who prefer to give birth by cesarean because they are afraid of pain or for other reasons, but it must kept in mind that recovery is much worse than with natural birth.…”
Section: Introductionmentioning
confidence: 99%